ВПЛИВ ЦИФРОВІЗАЦІЇ НА ФОРМУВАННЯ ЛЮДСЬКОГО КАПІТАЛУ: ВИКЛИКИ ТА МОЖЛИВОСТІ - Близнюк, Василь Миколайович (TIME DESCRIPTION OF ECONOMIC REFORMS, 2025)
The accelerated digitalization of socio-economic processes creates an unprecedented dialectical unity of challenges and opportunities in human capital formation, necessitating a rethinking of approaches to its development. The aim of the research. Theoretical and methodological substantiation of digitalization's impact on human capital formation through systematization of scientific views' evolution and development of an assessment matrix for enterprise digital maturity influence. The subject of the research. Processes of human capital formation and development in the context of digital transformation of economy and society. The methods of the research. The methodology is based on a dialectical approach to analyze the unity of digitalization challenges and opportunities, a systematic approach to examine digital maturity, comparative analysis of international experience, and a matrix approach to assess digital maturity impact. The hypothesis of the research. Enterprises with higher levels of digital maturity create a more favorable environment for human capital development through effective utilization of digital technologies. The statement of basic materials. The dialectical unity of digitalization challenges and opportunities has been revealed. The periodization of human capital concept evolution identified stages from economic resource to hybrid intelligence paradigm. The proposed matrix enabled identification of nine scenarios of interaction between digitalization level and human capital development. The originality and practical significance of the research. A matrix approach for evaluating the relationship between organizations' digital maturity and human capital development is proposed. The matrix serves as a practical tool for diagnostics and determining human capital development directions. Conclusions and perspectives of further research. The stages of human capital concept development have been established, and the necessity of a systematic approach to digital transformation management has been proven. Further research will focus on empirical verification of the matrix and development of methodological tools for assessing investment efficiency in digital competencies development